2015
DOI: 10.1177/0301006615599905
|View full text |Cite
|
Sign up to set email alerts
|

Migraine in Synesthetes and Nonsynesthetes: A Prevalence Study

Abstract: Synaesthesia is a neurological condition in which an inducer stimulus in one sense leads to a concurrent percept in a second sense. The immune hypothesis of synaesthesia links synaesthesia to immune-related conditions such as migraine. More specifically, migraine with aura may be linked to grapheme-colour synaesthesia as both involve cortical hyperexcitability. In this study, 188 synaesthetes and 121 non-synaesthetes completed an online questionnaire about synaesthesia and migraine. We found no general link be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
6
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 40 publications
1
6
1
Order By: Relevance
“…Given that this test is sensitive to the presence of migraine, it is important to note that the participants of this study, synaesthetes and controls, reported a low incidence of migraine with aura (syns = 4.3%, controls = 9.4%) and migraine without aura (syns = 8.7%, controls = 13.2%) and did not differ from each other in this regard (Fisher’s test p = 0.634; and p-.688 respectively), as noted by a previous study34.…”
Section: Resultssupporting
confidence: 73%
“…Given that this test is sensitive to the presence of migraine, it is important to note that the participants of this study, synaesthetes and controls, reported a low incidence of migraine with aura (syns = 4.3%, controls = 9.4%) and migraine without aura (syns = 8.7%, controls = 13.2%) and did not differ from each other in this regard (Fisher’s test p = 0.634; and p-.688 respectively), as noted by a previous study34.…”
Section: Resultssupporting
confidence: 73%
“…Our study could not address previous questions concerning RIS/MS and synaesthesia due to small sample sizes, and we found no link between synaesthesia and IBS (Carruthers et al, 2012) nor migraine (Jonas & Hibbard, 2015) although we did not discriminate between different headache/migraine phenomena. Another limitation of our study was that we investigated diagnosed health conditions only, which might have underrepresentation certain health conditions where people may be less likely to seek medical help.…”
Section: Discussioncontrasting
confidence: 99%
“…With less formal screening (self-declared), Jonas and Hibbard (2015) questioned 253 female participants about both synaesthesia and migraine and found that certain types of synaesthetic triggers (scents, tastes, emotions, personalities, and visual triggers) were associated with higher rates of headache with visual disturbances. With less formal screening (self-declared), Jonas and Hibbard (2015) questioned 253 female participants about both synaesthesia and migraine and found that certain types of synaesthetic triggers (scents, tastes, emotions, personalities, and visual triggers) were associated with higher rates of headache with visual disturbances.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…6 Both excess and lack of sleep can trigger migraine attacks. 7 Also synesthesia, a condition from which Tesla suffered, can be associated with migraine 8 ("when a word was spoken to me the image of the object it designated would present itself vividly to my vision"). 1 Based on the description of his "many strange likedislike habits," eg, the violent aversion against the earrings of women, the hair of other people or the germs, or the need that "all repeated acts or operations I performed had to be divisible by three," 1 we also propose that Tesla suffered from an obsessive-compulsive disorder.…”
mentioning
confidence: 99%